(untitled) (Research, Society and Development, 2022)
Introduction: stress is the major cause of changes in the immune responses in the human body and are defined as a state of disharmony or threatened homeostasis. The importance of understanding the mechanisms of action of stress and their impacts on the immune system is perceived. Objective: to identify the impacts of stress on the immune system and what are its mechanisms of action. Methodology: a study carried out through an integrative literature review, of an exploratory and qualitative, non-systematic nature, through bibliographic research in the Lilacs, BVS (Virtual Health Library) and Scielo databases, with the combination of the descriptors: AND immune system Immunity AND Stress. Articles published between 2010 and 2020, in English or Portuguese, with full texts available for free were included. Results: the search resulted in 126 articles, which after applying the inclusion criteria totaled 04 studies. Conclusion: it was possible to observe that stress causes a negative impact on the immune system. These changes in the immune system can lead to a predisposition to the appearance of some diseases, which arise when there is an immune imbalance.